Experimental Study on Hollow Steel Sections Under Elevated Temperature - Prakash Murugan; Alireza Bahrami; Vishal Murugan; Ajish Kumaran (Civil Engineering Journal, 2024)
Structures known as modular buildings are made in factories and then moved to construction sites, where they are assembled. The efficacy of modular structures under many uncertainties has to be thoroughly investigated as demand rises; fire is one such uncertainty. The purpose of this study is to ascertain how high temperature affects the components of modular constructions. In the current study, hollow steel columns and beams were taken into account as components of a modular construction. Using ABAQUS, several situations were examined depending on the span length to determine the important locations of the members. Experimental research was conducted on the critical regions identified by the analysis, and the results were contrasted with those of the analysis. A high-temperature localized heating furnace was used for the experimental testing. The findings demonstrated that for spans of 250 mm and 500 mm, the central area of the beams was essential, and the load-carrying capacity was six times less than that of heating at the extremities of the beams. Similar to the beams, columns exhibited less fluctuation than the beams and were weaker in the bottom area when exposed to high temperature. When compared to other places, the capacity was reduced by 1.1 times, and in Case 1, the capacity reduction with regard to loading was 1.68 times greater. Doi: 10.28991/CEJ-2024-010-03-014 Full Text: PDF